Incidence of Complications in Obese Patients Undergoing Elective Spine Surgery Under General Anesthesia: A Retrospective Study - Boonsombat, Thanachporn; Akavipat, Phuping; Suchartwatnachai, Pathomporn; Sookplung, Pimwan; Eiamcharoenwit, Jatuporn; Chotisukarat, Haruthai (Journal of Neuroanaesthesiology and Critical Care, 2024)
Background The prevalence of obesity has been increasing worldwide. Simultaneously, the number of obese patients undergoing anesthesia and the risk of anesthesia-related complications are increasing. Our study aimed to identify the incidence of intraoperative anesthetic complications in obese patients undergoing elective spine surgery.Methods Electronic medical records of patients with a body mass index (BMI) ≥ 30 kg/m2 who underwent elective spine surgery at the Neurological Institute of Thailand between January 2018 and December 2020 were retrospectively reviewed. The primary outcome was the incidence of five anesthetic adverse events: difficult intubation, oxygen desaturation, hypotension, major adverse cardiac and cerebrovascular events (MACCE), and pressure skin lesions. Logistic regression was used for statistical analysis.Results A total of 165 obese patients' medical records were analyzed. Their mean age was 56.8 ± 11.9 years, and median BMI (interquartile range) was 32.04 kg/m2 (31.11–34.69 kg/m2). Fifty-one patients (30.9%) experienced adverse events. Six patients (3.6%) with class 3 obesity had anesthetic complications. The most common adverse event was intraoperative hypotension (26.7%), followed by pressure skin lesions (4.2%), intraoperative oxygen desaturation (1.2%), and MACCE (0.6%). No difficult intubations or deaths occurred.Conclusion The incidence of overall intraoperative anesthetic complications in obese patients undergoing spine surgery was 30.9%, and class 3 obesity was an independent risk factor for these complications. Consequently, well-trained, vigilant, and experienced anesthesiologists should manage anesthesia in these patients.
Keywords: general anesthesia; complications; obesity; spine surgery